Pre- and postoperative developmental attainment in sagittal synostosis. Issue 4 (21st March 2005) - Bellew, M; Chumas, P; Mueller, R; Liddington, M; Russell, J
Abstract : Aims: To investigate whether sagittal synostosis (SS) has consequences for children's mental and psychomotor development, and whether surgery has any impact on this. Methods: The study involved 28 children with SS who underwent corrective surgery at a mean age of 8.0 (SD 7.16) months, and 28 normal controls. All the children with SS were assessed pre- and postoperatively using the Griffiths Mental Development Scales. The controls were assessed on one occasion, at an age matched with individuals in the patient group at the time of the preoperative assessment. A further control group consisted of 13 children with SS, who had received developmental assessment on two or more occasions without surgical intervention. Results: The data indicated that children with SS have significantly poorer gross locomotor function than the normal controls. Following surgical intervention the deficit was shown to have resolved; consistent with this a lesser improvement in eye-hand coordination and performance skills was shown. Overall developmental attainment also improved postoperatively. The children with SS who did not receive surgery did not show any improvement in development. Conclusions: The study shows improved developmental attainment following surgical correction of SS, which may therefore be more than a cosmetic procedure.